Interplay between erodent concentration and impingement angle for erosion in dilute water-sand flows - Grewal, H. S.; Singh, H.; Yoon, Eui-Sung (ELSEVIER SCIENCE SA, 2015)
Slurry erosion is a complex process with number of interacting variables (operating and material parameters). We study the interaction between erodent concentration and impingement angle using experimental and computational fluid dynamics (CFD) techniques. Experiments were performed using a high velocity slurry erosion test rig at a constant velocity with dilute slurries of water and sand particles. Concentration of sand in water was varied from 0.01 wt% (100 ppm) to 0.5 wt% (5000 ppm) at three sample orientations (30 degrees, 60 degrees and 90 degrees). Six different targets, three bulk materials (aluminum, cast iron, and stainless steel) and three thermal sprayed coatings (Ni + 20, 40, and 60 wt% of Al2O3) were used for slurry erosion tests. Experimental results showed a significant interaction between erodent concentration and impingement angle. The concentration variation showed larger influence on erosion rate for sample held normal to the slurry jet compared to glancing angle. The degree of interaction was different for different materials. CFD simulations showed higher particle-to-particle interactions for sample at glancing angle compared to that at normal angle. This probably explains the low contribution of concentration variation at glancing angle compared to the normal angle. Further, the effect of concentration on erosion rates was also influenced by the restitution coefficient (function of material and impact parameters). For a high restitution coefficient materials, the change in slurry concentration showed minimum effect on erosion rate compared with low restitution coefficient materials. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: SOLID PARTICLE EROSION; SLURRY-EROSION; COMPOSITE COATINGS; DUCTILE METALS; WEAR; CORROSION; JET; PREDICTION; MECHANISM; TESTER